Uji Penentuan Nilai SPF (Sun Protection Factor) Fraksi Bunga Rosela (Hibiscus Sabdariffa L.) Sebagai Zat Aktif Tabir Surya - Nopiyanti, Vivin; Aisiyah , Siti (Jurnal Farmasi (Journal of Pharmacy), 2020)
Sun Protection Factor or SPF is defined as the ratio between the amount of sunlight energy (in this case UV-B) needed to cause minimal erythema on sun-protected skin with the amount of energy needed to cause minimal erythema on skin that is not protected by sunscreen. Rosela flowers contain flavonoids, anthocyanes, and polyphenols. Flavonoids compound have the potential as sunscreens because they have a chromophore group (single conjugated double bond) that is able to absorb UV-A and UV-B rays so that it reduces the intensity of the skin. This research was conducted to find out the SPF value of the n-hexane fraction, the ethyl acetate fraction and the water fraction from the rosela flower. And it is known that the faction that has the highest SPF value can be used as sunscreen. Rosela flower extract then fractionated with n hexane, ethyl acetate and water solvents. The resulting fractions in the form of n-hexane fraction, ethyl acetate fraction and water and extract fractions were measured for their SPF values. SPF measurements can be done in vitro using UV-Vis spectrophotometry. In vitro testing was useful for preliminary tests in the process of developing sunscreen products. The SPF value of the extract, the n-hexane fraction, the ethyl acetate fraction and the water fraction from the rosela flower extract, respectively 6,63±0,23; 10,11±0,61; 13,83±1,50; 11,15±0,47. The ethyl acetate fraction was the fraction that has the highest SPF value that can be used as a sunscreen.